The Influence of Motivation and Organisational Culture on The Performance of Non-Lecturer Employees of Mercu Buana University With Organisational Commitment As An Intervening Variable - Yusri Saleh; Masydzulhak Djamil (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study is to investigate the effect of an organisation's culture and motivation at work on the performance or performance of non-lecturer employees at Mercu Buana University, by considering the role of organisational commitment as an intermediate variable. The method approach to be used is quantitative, and the research population consists of 278 permanent employees who are not lecturers at Mercu Buana University. The sample to be used in the study is 74 people, with an error rate of 10% based on the slovin formula. Primary data will be obtained through the use of questionnaires, observations, literature studies, and information sources from internet research. Data analysis and testing will be carried out using SEM-PLS which is processed using the SmartPLS application. The results obtained based on testing are that the culture that exists in the organisation has a positive impact on the quality of employee performance. In addition, it was found that organisational culture also has a positive effect on organisational commitment, which also plays a role in mediating the effect of organisational culture on employee performance. Work motivation also has a positive impact on employee performance, and organisational commitment acts as a significant mediator variable in connecting the effect of work motivation on employee performance.